2014
DOI: 10.1039/c3tc32318h
|View full text |Cite
|
Sign up to set email alerts
|

Dual-emission of silicon quantum dots modified by 9-ethylanthracene

Abstract: Dual-emissive silicon quantum dots were successfully achieved by surface modification with 9-ethylanthracene as a functional ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 57 publications
1
38
0
Order By: Relevance
“…The second group includes metals with a ratio lower than 1.633 as Zr (1.589) and Ti (1.587), with a AE 20-408 tilted texture from the normal direction toward the transverse direction. [55] The third group includes materials with about equal ratio than the ideal value of 1.633, such as Mg, and that tend to form basal fiber textures during rolling. From the literature, [56,57] it was found that e-martensite can be included in the second group, together with Zr and Ti.…”
Section: Microtexture Analysismentioning
confidence: 99%
“…The second group includes metals with a ratio lower than 1.633 as Zr (1.589) and Ti (1.587), with a AE 20-408 tilted texture from the normal direction toward the transverse direction. [55] The third group includes materials with about equal ratio than the ideal value of 1.633, such as Mg, and that tend to form basal fiber textures during rolling. From the literature, [56,57] it was found that e-martensite can be included in the second group, together with Zr and Ti.…”
Section: Microtexture Analysismentioning
confidence: 99%
“…For continuous distillation applications especially the so‐called rotating zigzag beds (RZBs), mainly developed by Wang et al , , have shown superior performance compared to known single‐block packings in RPB and have resulted in a number of industrial applications, primarily in Asia , . Unlike classical RPBs with so‐called single‐block packings , which are fixed in between two simultaneously rotating disks, the RZB rotor consists of a rotating disk and a stationary disk, on which two series of circular baffles are mounted in an alternating fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the as-extruded Mg alloys exhibit intensive fiber texture with basal planes paralleled to extrusion direction. [45] The deformation mechanisms largely relies on the orientation of the applied stress and texture due to the low symmetry of Mg alloys. The basal slip with lowest critical resolved shear stress (CRSS) was inhibited when the tensile direction paralleled to extrusion direction.…”
Section: Resultsmentioning
confidence: 99%